The implementation of public relation Program Nasional Senyum Indonesia as management strategy in upholding autoimmune awareness - Rai, Switha Kathline (Management and Entrepreneurship: Trends of Development, 2020)
Autoimmune categorized as a dangerous non-communicable disease that tends to be at bigger risk for women and children. Lack of understanding on general public and medical experts has an impact to the high mortality rate from autoimmune diseases.Having a response to the fact, Marisza Cardoba Foundation as a non-governmental organization concerned with health inaugurated the Senyum Indonesiaku National Program along with the Ministry of Women's Empowerment and Child Protection to support public awareness of autoimmune. The purpose of this research is to understand and analyze the implementation of one of the program strategies. This study uses Harold Laswell's communication theory and public relations campaign by Ronald D. Smith.The research method used is a descriptive-qualitative approach. The research finding found that Idolanesia Awards Indonesia 2017as one of the strategies for Senyum Indonesiaku National Program, include as good effort to support public awareness regarding the autoimmune. However, weaknesses were still found in the planning strategies of the program.JEL Classification:  H750, I10, I12